Elastic constants of Ni[sub 3](Al,Mn) + B from 180 to 613 K - Kuokkala, V.T.; Tiainen, T.; Vuorinen, J. (Scripta metallurgica et materialia, 1993)
Intermetallic compounds have been the subject of increasingly intensive research in recent years, primarily because of their great potential for high temperature applications. Alloy development, especially improvement of inherently poor ductility of intermetallics has been the focus of the research work, but much effort has also been put to the determination of the mechanical properties of these alloys. For any material of scientific or practical interest, one of the fundamental properties to be determined is the elastic constants or elastic moduli of the material. In the characterization of materials, the elastic moduli are of special importance. They relate microscopically measurable physical properties directly to atomic level interactions in the crystal lattices or in the disordered arrangement of atoms in amorphous materials. For both scientific and technical purposes, it is also desirable to know how the elastic moduli of the material change with temperature. To extend the measuring range of rectangular parallelepiped resonance method to higher temperatures, the authors have developed a new non-contact measurement technique, based on magnetostrictive excitation and detection of the resonances in the sample. This technique is applicable form cryogenic temperatures up to about 950 C. In this work, the authors used this new measurement technique to determine the elastic constants of Mn- and B-modified polycrystalline Ni[sub 3]Al intermetallic alloy in the temperature range 180--613 K. Both manganese and boron have been observed to improve the ductility of Ni[sub 3]Al.